Implications of labor supply specifications in CGE models: A demonstration for employment of Palestinian labor in Israel and its impact on the West Bank economy - Johanes Agbahey; Khalid Siddig; Harald Grethe (Humboldt-Universität zu Berlin, Faculty of Life Sciences, Department of Agricultural Economics, 2020)
Results of general equilibrium models are sensitive to model parameterization and specification. The role of macroeconomic closures and the effect of trade elasticities are documented in the literature, but there is no systematic analysis of the implications of different labor supply specifications for the effect of shocks to labor markets. This study analyzes these implications, using data for the West Bank economy and a general equilibrium model with four different labor market specifications. The findings indicate that increased Palestinian employment in Israel leads to changes in real GDP in the range of -1.8% to +3.4%, depending on the model specification. This wide range of effects on macroeconomic aggregates stems from the definition of the production boundary, the implicit assumptions on the opportunity cost of labor in activities outside the production boundary, and the conditions for a transfer of labor across the boundary. Economic theory indicates that the labor-leisure trade-off is the most consistent framework for modeling labor supply decisions. However, in the absence of data for activities outside the SNA boundary, the full-employment assumption may be the second-best alternative, although it risks overstating the changes in real wage rates. The surplus labor and upward-sloping labor supply curve specifications both tend to understate the increases in wage rates and overstate the welfare gains.
Keywords: D13; D58; E24; J21; J22; J60; 330; Labor-leisure; labor mobility; production boundary; unemployment; general equilibrium models; Palestine